The South China Sea disputes : is the Aquino Way the "ASEAN Way"? - Pablo-Baviera, Aileen San (2012)
Growing Chinese assertiveness and military capability have led the Aquino government to adopt tougher rhetoric towards China over the South China Sea disputes. Will the Aquino way bring more results than the “ASEAN Way”?